Altered spatial summation optimizes visual function in axial myopia - Stapley, Victoria; Anderson, Roger S.; Saunders, Kathryn J.; Mulholland, Pádraig J. (Scientific reports, 2020)
This study demonstrates significant differences between the area of complete spatial summation (Ricco’s area, RA) in eyes with and without non-pathological, axial myopia. Contrast thresholds were measured for six stimuli (0.01–2.07 deg 2 ) presented at 10º eccentricity in 24 myopic subjects and 20 age-similar non-myopic controls, with RA estimated using iterative two-phase regression analysis. To explore the effects of axial length-induced variations in retinal image size (RIS) on the measurement of RA, refractive error was separately corrected with (i) trial lenses at the anterior focal point (near constant inter-participant RIS in mm), and (ii) contact lenses (RIS changed with axial length). For spectacle corrected measurements, RA was significantly larger in the myopic group, with a significant positive correlation also being observed between RA and measures of co-localised peripheral ocular length. With contact lens correction, there was no significant difference in RA between the groups and no relationship with peripheral ocular length. The results suggest RA changes with axial elongation in myopia to compensate for reduced retinal ganglion cell density. Furthermore, as these changes are only observed when axial length induced variations in RIS are accounted for, they may reflect a functional adaptation of the axially-myopic visual system to an enlarged RIS.